PENGARUH EKSTRAK DAUN SIRIH (Piper betle L) TERHADAP MORTALITAS WALANG SANGIT - Diana Buulolo (Universitas Nias Raya, 2023)
This research is motivated by the use of chemical pesticides that cause pollution and are harmful to health. This study aims to determine the effect of betel leaf extract (Piper betle L) on the mortality of walang sangit. This research method is a quantitative data collection technique used in observation and documentation studies. Research has shown that betel leaf extract has the ability to control the movement and death of stink bugs. The process of making betel leaf extract is very simple, effective, does not require large costs and is environmentally friendly. Based on the results of the study, betel leaf extract can be used as a natural insecticide to control stink bugs because it contains the active ingredient tannins, toxic substances (toxins) that can reduce the mortality movement of stink bugs.